Diaphragm porosity testing method
By using water as a medium and a lithium battery separator porosity analyzer for separator porosity testing, the problems of high testing costs, low safety and low accuracy in the prior art are solved, and safe, economical and accurate porosity evaluation are achieved. , improving the accuracy of lithium battery performance evaluation.
Patent Information
- Application Number
- CN202411671537.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-01-10
AI Technical Summary
The existing separator porosity testing methods have problems such as high testing cost, low safety and low accuracy, especially the use of harmful solvents and destructive testing methods, which affect the accuracy of battery performance evaluation.
Water is used as the medium and tested by a lithium battery separator porosity analyzer. Combining the basic parameters and preset parameters of the diaphragm sample, non-destructive testing is achieved, and the porosity of through holes and blind holes can be evaluated simultaneously.
It reduces testing costs, improves safety and accuracy, provides an accurate evaluation of lithium battery performance, and contributes to quality control and diaphragm optimization during R&D.
Smart Images

Figure CN119290708A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of diaphragm testing, and in particular to a diaphragm porosity testing method. Background Art
[0002] Lithium-ion batteries are widely used because of their advantages such as high voltage, high capacity, long cycle life and no memory effect. For lithium-ion batteries, the characteristics of the diaphragm material and related processing technology have a great influence on their performance. Among them, the porosity of the diaphragm is a crucial parameter information, and the size of the diaphragm porosity affects the comprehensive performance of lithium batteries.
[0003] The porosity of the diaphragm directly affects the permeability of the diaphragm and the capacity of the electrolyte, which in turn affects the internal resistance, high-temperature storage performance, rate discharge performance and cycle performance of the battery. Specifically, when the porosity of the diaphragm increases, the internal resistance of the battery will decrease. This is because the high-porosity diaphragm provides more ion transmission channels, making the migration of lithium ions in the diaphragm smoother, thereby reducing the internal resistance of the battery. When the porosity of the diaphragm increases, it will cause the performance of the battery to decrease during high-temperature storage. This is because the high-porosity diaphragm is more likely to absorb electrolyte at high temperatures, resulting in increased internal pressure in the battery, which may affect the safety and life of the battery.
[0004] Moreover, when the porosity of the diaphragm increases, the diaphragm can provide more ion transmission channels during high current discharge to improve the rate discharge performance of the battery. However, during low current discharge, the effect of porosity is small. When the porosity of the diaphragm increases, the diaphragm can better adapt to the flow of electrolyte during the cycle, thereby reducing the aging rate of the electrode and increasing the cycle life of the battery. When the porosity of the diaphragm increases, the diaphragm can accommodate more electrolyte, thereby improving the electrochemical performance and safety of the battery.
[0005] At present, the methods for testing the porosity of diaphragms in the industry include the imbibition method, the calculation method, and the mercury injection method. Among them, the imbibition method is simple and easy, but the testing process requires the use of organic reagents such as anhydrous ethanol, hexadecane, and n-butanol, which is costly and has certain hazards to the human body and the environment; the results calculated by the calculation method include three pore structures: through holes, blind holes, and closed holes. However, it is the through holes that actually affect the battery performance, making this method unable to accurately evaluate the impact of the diaphragm porosity on the battery. The mercury injection method uses a medium mercury that is toxic to a certain extent and can easily cause harm to humans and the environment. In addition, the destructive test of the test samples is costly.
[0006] Therefore, the membrane porosity testing method in the prior art has the problems of high testing cost, low testing safety, and low testing accuracy, which is not conducive to improving the accuracy of battery performance evaluation. Summary of the invention
[0007] In view of this, the present invention aims to propose a membrane porosity testing method, which can improve the safety and accuracy of the testing process and achieve cost-saving design.
[0008] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0009] A method for testing the porosity of a diaphragm comprises the following steps:
[0010] preparing a membrane sample and obtaining basic sample parameters of the membrane sample;
[0011] Completely soaking the membrane sample with water;
[0012] The diaphragm sample placed in the sample tank after being soaked is tested by a lithium battery diaphragm porosity analyzer with preset parameters and basic parameters of the sample to obtain actual test parameters of the diaphragm sample;
[0013] The porosity δ of the diaphragm sample is obtained according to the actual test parameters.
[0014] Furthermore, the basic parameters of the sample include the weight M and density ρ of the diaphragm sample.
[0015] Furthermore, the preparation of the membrane sample also includes the following steps: selecting a flat and wrinkle-free membrane, and cutting the membrane to obtain the membrane sample.
[0016] Furthermore, when obtaining the basic parameters of the sample, the following steps are also included: obtaining the length dimension a, width dimension b and thickness dimension c of the diaphragm sample, and calculating the volume V of the diaphragm sample; obtaining the weight M of the diaphragm sample, and obtaining the density ρ based on the volume V and the weight M of the diaphragm sample.
[0017] Furthermore, the volume V of the diaphragm sample is ≥ 1 cm 3 .
[0018] Furthermore, before the diaphragm sample is completely soaked with water, the following steps are also included: cutting the diaphragm sample into multiple sections with a preset width x, and obtaining the weight M based on the cut multiple sections of the diaphragm sample.
[0019] Furthermore, before the diaphragm sample soaked in the sample slot is tested by the lithium battery diaphragm porosity analyzer with preset parameters and the basic parameters of the sample, the following steps are also included: placing multiple sections of the diaphragm sample completely soaked with water into the sample slot, and placing the sample slot in the lithium battery diaphragm porosity analyzer.
[0020] Furthermore, the preset parameters include the test pressure P and the number of data sampling points.
[0021] Furthermore, the test pressure P is between 20-1500 psi; and / or the number of data points is between 50-200.
[0022] Furthermore, before testing the membrane sample placed in the sample slot after being soaked by the lithium battery membrane porosity analyzer with preset parameters and the basic parameters of the sample, the following steps are also included: testing the empty sample slot by the lithium battery membrane porosity analyzer to obtain blank test parameters;
[0023] When the porosity of the diaphragm sample is obtained according to the actual test parameters, the method further includes the following steps: obtaining the porosity δ of the diaphragm sample according to the actual test parameters and the blank test parameters.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] The diaphragm porosity testing method described in the present invention uses water as a medium, which is not only low in cost, but also can avoid affecting the human body and the environment compared to the use of harmful solvents such as mercury and hexadecane in the prior art, thereby improving the safety of the testing process. At the same time, combined with the characteristics of the lithium battery diaphragm porosity analyzer that the diaphragm sample volume is large, the test pressure is small, and both through holes and blind holes can be tested at the same time, the diaphragm can be used as a hydrophobic material to perform porosity testing, thereby realizing non-destructive testing of diaphragm samples and making the test results more accurate, thereby facilitating the improvement of the accuracy of battery performance evaluation and facilitating quality control in the research and development and production process of lithium battery diaphragms. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0027] Figure 1 This is a flow chart of the membrane porosity testing method according to an embodiment of the present invention;
[0028] Figure 2 This is a curve chart of test results obtained by the lithium battery diaphragm porosity analyzer described in an embodiment of the present invention. DETAILED DESCRIPTION
[0029] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0030] The present invention will be described in detail below with reference to the accompanying drawings and in conjunction with embodiments.
[0031] The present embodiment relates to a membrane porosity testing method, which helps to solve the problems of high testing cost, low testing safety, and low testing accuracy in existing membrane porosity testing methods.
[0032] In terms of overall design, Figure 1 As shown, the membrane porosity testing method of this embodiment includes the following steps:
[0033] S1, preparing a membrane sample and obtaining basic sample parameters of the membrane sample;
[0034] S2, completely soak the membrane sample with water;
[0035] S3, using a lithium battery diaphragm porosity analyzer to test the diaphragm sample after being soaked in the sample tank with preset parameters and basic sample parameters, and obtain the actual test parameters of the diaphragm sample;
[0036] S4, the porosity δ of the diaphragm sample is obtained according to the actual test parameters.
[0037] At this time, as designed above, since water is used as the medium, it is not only low-cost, but also can avoid affecting the human body and the environment compared to the use of harmful solvents such as mercapto and hexadecane in the prior art, thereby improving the safety of the testing process. At the same time, combined with the large volume of the diaphragm sample required for the lithium battery diaphragm porosity analyzer test, the test pressure is small, and the through holes and blind holes can be tested at the same time. The porosity test can be carried out by utilizing the hydrophobic material properties of the diaphragm to achieve non-destructive testing of the diaphragm sample and make the test results more accurate, thereby facilitating the improvement of the accuracy of battery performance evaluation and facilitating quality control in the research and development and production process of lithium battery diaphragms.
[0038] Based on the above design concept, in detail, in this embodiment, due to the realization of non-destructive testing of the diaphragm sample during the specific design, it also has the effect of reducing costs to a certain extent. At the same time, as a preferred implementation form, when the diaphragm sample is completely infiltrated with water, the following steps may also be included: water is pressed into the diaphragm sample at different pressures by a water pressure instrument to completely infiltrate the diaphragm sample.
[0039] In this embodiment, as a preferred implementation form, the basic parameters of the sample include the weight M and density ρ of the membrane sample. In specific implementation, preparing the membrane sample also includes the following steps: selecting a flat and wrinkle-free membrane, cutting the membrane to obtain a membrane sample.
[0040] In addition, when obtaining the basic parameters of the sample, the following steps are also included: obtaining the length dimension a, width dimension b and thickness dimension c of the diaphragm sample, and calculating the volume V of the diaphragm sample. Obtaining the weight M of the diaphragm sample, and obtaining the density ρ according to the volume V and weight M of the diaphragm sample.
[0041] In this embodiment, the size of the membrane sample can be measured by a steel ruler, and then the membrane without wrinkles can be cut to obtain the membrane sample, as well as the length dimension a, width dimension b, and thickness dimension c of the membrane sample. The volume V of the membrane sample can be obtained by the expression V=a*b*c. At the same time, in this embodiment, the weight M can be obtained by weighing the membrane sample on a balance.
[0042] In this embodiment, as a preferred implementation form, the volume of the diaphragm sample V ≥ 1 cm 3 , for example, the volume V can be 1 cm 3 、1.5cm 3 or 2cm 3 Etc. Among them, the larger the volume V is, the more conducive it is to improving the test accuracy of the lithium battery diaphragm porosity analyzer.
[0043] In this embodiment, as a preferred implementation form, before the diaphragm sample is completely soaked with water, the following steps are also included: cutting the diaphragm sample into multiple sections with a preset width x, and obtaining a weight M based on the cut multiple sections of the diaphragm sample.
[0044] By cutting the membrane sample into multiple sections of preset width x, it is convenient to place the membrane sample in the sample slot later. At the same time, the weight M is obtained according to the cut multiple sections of the membrane sample, which is convenient to ensure the test accuracy of the weight M, and further to ensure the accuracy of the overall test result. Of course, the preset width x here can be preferably set between 1-3 cm, for example, specifically 1 cm, 2 cm or 2.5 cm, etc., so as to facilitate the convenience of placing the membrane sample in the sample slot.
[0045] In addition, in this embodiment, as a preferred implementation form, before testing the diaphragm sample after being soaked in the sample slot by the lithium battery diaphragm porosity analyzer with preset parameters and basic sample parameters, the following steps are also included: placing the multi-segment diaphragm sample completely soaked with water into the sample slot, and placing the sample slot in the lithium battery diaphragm porosity analyzer.
[0046] Moreover, in this embodiment, as a preferred implementation form, the preset parameters include the test pressure P and the number of data points. In specific implementation, the test pressure P can be preferably set between 20-1500psi, for example, 20psi, 500psi, 800psi, 1000psi, 1200psi or 1500psi.
[0047] It should be mentioned that since the diaphragm sample is a hydrophobic material, if the test pressure P is higher than 1500psi during the test, it is easy to cause the diaphragm sample to deform and rupture, causing hole deformation and affecting the test accuracy; if the test pressure P is lower than 20psi, it will affect the test efficiency.
[0048] Furthermore, the number of data points in this embodiment can be preferably set between 50-200, for example, specifically 50, 100 or 200, so as to be able to view the test data more intuitively and obtain more accurate test results. At the same time, the lithium battery diaphragm porosity analyzer in this embodiment can specifically adopt the lithium battery diaphragm porosity analyzer model AAQ-3K-A-1 of PMI Company of the United States.
[0049] In addition, in this embodiment, as a preferred implementation form, before testing the membrane sample placed in the sample slot after infiltration using the lithium battery membrane porosity analyzer with preset parameters and basic sample parameters, the following steps are also included: testing the empty sample slot using the lithium battery membrane porosity analyzer to obtain blank test parameters. And when the porosity of the membrane sample is obtained according to the actual test parameters, the following steps are also included: according to the actual test parameters and the blank test parameters, the porosity δ of the membrane sample is obtained.
[0050] The purpose of testing the empty sample slots is to perform a blank test before testing the diaphragm samples. Through the blank test, errors that may be introduced by the instrument itself, environmental factors, and operation processes can be eliminated, thereby improving the accuracy and reliability of the test results.
[0051] Secondly, the working principle of the lithium battery diaphragm porosity analyzer in this embodiment is: using the pressure difference principle, the pre-treated sample is placed between the upper and lower test chambers and clamped and sealed to form a constant pressure difference. Under the action of the pressure difference, the gas flows from the high-pressure side through the sample to the low-pressure side, and the porosity and air permeability of the diaphragm are evaluated by measuring the time it takes for the gas to pass through the diaphragm. In addition, the porosity δ of the diaphragm sample can be calculated by the expression δ=Vr / V*100% and the Washburn equation, where Vr is the cumulative pore volume. At this time, combined with Figure 2 As shown in, it is a test result curve obtained by a lithium battery diaphragm porosity analyzer, the horizontal axis represents the pore (pore size), and the vertical axis represents the cumulative pore volume under the corresponding horizontal axis. In addition, according to the diaphragm porosity test method of this embodiment, the porosity of most lithium-ion battery diaphragms is between 30% and 50%.
[0052] The diaphragm porosity testing method of the present embodiment uses water as the medium, which is not only low-cost, but also can avoid the impact on the human body and the environment compared to the use of harmful solvents such as mercapto and hexadecane in the prior art, thereby improving the safety of the testing process. At the same time, combined with the characteristics of the lithium battery diaphragm porosity analyzer that the diaphragm sample volume is large, the test pressure is small, and both the through holes and blind holes can be tested at the same time, the diaphragm can be used as a hydrophobic material to perform porosity testing, thereby realizing non-destructive testing of diaphragm samples and making the test results more accurate, thereby facilitating the improvement of the accuracy of battery performance evaluation and facilitating quality control in the research and development and production process of lithium battery diaphragms.
[0053] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for testing the porosity of a diaphragm, characterized in that: The following steps are involved: preparing a membrane sample and obtaining basic sample parameters of the membrane sample; Completely soaking the membrane sample with water; The diaphragm sample placed in the sample tank after being soaked is tested by a lithium battery diaphragm porosity analyzer with preset parameters and basic parameters of the sample to obtain actual test parameters of the diaphragm sample; The porosity δ of the diaphragm sample is obtained according to the actual test parameters.
2. The diaphragm porosity testing method according to claim 1, characterized in that: The basic parameters of the sample include the weight M and density ρ of the membrane sample.
3. The membrane porosity testing method according to claim 2, characterized in that: The preparation of the membrane sample further comprises the following steps: A flat and wrinkle-free diaphragm is selected and cut to obtain the diaphragm sample.
4. The diaphragm porosity testing method according to claim 3, characterized in that: When obtaining the basic parameters of the sample, the following steps are also included: Obtaining the length dimension a, width dimension b and thickness dimension c of the diaphragm sample, and calculating the volume V of the diaphragm sample; The weight M of the diaphragm sample is obtained, and the density ρ is obtained according to the volume V and the weight M of the diaphragm sample.
5. The method for testing the diaphragm porosity according to claim 4, characterized in that: The volume of the membrane sample V ≥ 1 cm 3 .
6. The membrane porosity testing method according to claim 3, characterized in that: Before the membrane sample is completely soaked with water, the following steps are also included: The diaphragm sample is cut into multiple sections with a preset width x, and the weight M is obtained based on the cut multiple sections of the diaphragm sample.
7. The membrane porosity testing method according to claim 6, characterized in that: Before testing the membrane sample placed in the sample tank after being soaked by the lithium battery membrane porosity analyzer with preset parameters and the basic parameters of the sample, the following steps are also included: Put multiple sections of the membrane samples completely soaked with water into the sample slot, and place the sample slot in the lithium battery membrane porosity analyzer.
8. The membrane porosity testing method according to claim 1, characterized in that: The preset parameters include the test pressure P and the number of data sampling points.
9. The method for testing the porosity of a diaphragm according to claim 8, characterized in that: The test pressure P is between 20-1500 psi; and / or, The number of data points is between 50 and 200.
10. The membrane porosity testing method according to any one of claims 1 to 9, characterized in that: Before testing the membrane sample placed in the sample tank after being soaked by the lithium battery membrane porosity analyzer with preset parameters and the basic parameters of the sample, the following steps are also included: The vacant sample slot is tested by the lithium battery diaphragm porosity analyzer to obtain blank test parameters; When the porosity of the diaphragm sample is obtained according to the actual test parameters, the following steps are also included: The porosity δ of the diaphragm sample is obtained according to the actual test parameters and the blank test parameters.
Citation Information
Cited By
Visual coating isolating membrane porosity testing method and system
CN120489897A
A visualized coating release film porosity test method and system
CN120489897B